2015
DOI: 10.1021/acs.biomac.5b01203
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Cellulolytic Enzymes with Native, Autohydrolysis, and Technical Lignins and the Effect of a Polysorbate Amphiphile in Reducing Nonproductive Binding

Abstract: Understanding enzyme-substrate interactions is critical in designing strategies for bioconversion of lignocellulosic biomass. In this study we monitored molecular events, in situ and in real time, including the adsorption and desorption of cellulolytic enzymes on lignins and cellulose, by using quartz crystal microgravimetry and surface plasmon resonance. The effect of a nonionic surface active molecule was also elucidated. Three lignin substrates relevant to the sugar platform in biorefinery efforts were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 71 publications
(183 reference statements)
2
42
3
Order By: Relevance
“…Molecular interactions between cellulase and hydrophobic tips were 13% and 43% higher than those with tips carrying ‐COOH and ‐OH groups, respectively . Rojas et al combined AFM and quartz crystal microgravimetry (QCM) to examine the interactions between cellulase and different lignin films and demonstrated the dominating effect of hydrophobic interactions on the lignin affinity of enzymes, while electrostatic interactions exhibited a minor effect in the reaction . Kinetic analysis based on QCM showed that Cel7B binding to lignin films only fitted the two‐site transition model, which suggests that Cel7B can bind reversibly to two distinct sites in a lignin surface at different adsorption rates .…”
Section: Interactions Between Lignin and Cellulase Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular interactions between cellulase and hydrophobic tips were 13% and 43% higher than those with tips carrying ‐COOH and ‐OH groups, respectively . Rojas et al combined AFM and quartz crystal microgravimetry (QCM) to examine the interactions between cellulase and different lignin films and demonstrated the dominating effect of hydrophobic interactions on the lignin affinity of enzymes, while electrostatic interactions exhibited a minor effect in the reaction . Kinetic analysis based on QCM showed that Cel7B binding to lignin films only fitted the two‐site transition model, which suggests that Cel7B can bind reversibly to two distinct sites in a lignin surface at different adsorption rates .…”
Section: Interactions Between Lignin and Cellulase Enzymesmentioning
confidence: 99%
“…An obvious fact is that Cel7A strongly binds lignin under a pH above its pI, which suggests the Coulombic repulsion can be overcome by the hydrophobic interactions . Direct evidences are also available from the measurement of AFM attractive force between cellulase and functional groups and the QCM adsorption studies varying with lignin and pH . Charge engineering of cellulase could be achieved by chemically derivatization of enzyme (e.g.…”
Section: Interactions Between Lignin and Cellulase Enzymesmentioning
confidence: 99%
“…Hence, the electrostatic repulsion force between the Avicel-LS complexes and cellulase after adding LS was larger than that between Avicel and cellulase before adding LS. It has been well known that electrostatic repulsion force exists among the particles which have the same charges and is the important interaction between cellulose and cellulase [27,28]. The larger electrostatic repulsion force caused more desorption of cellulase from the Avicel particles, which resulted in less total adsorption amount of cellulase on the Avicel-LS complexes than Avicel.…”
Section: The Total Adsorption Of Cellulase On Avicelmentioning
confidence: 99%
“…Removing lignin has been proven to dramatically improve the cellulose enzymatic digestibility of lignocelluloses . Lignin can be removed by various chemical processes, among them an oxidative process can substantially modify the lignin structure and decrease surface hydrophobicity that has been known as a main factor for non‐productive adsorption of cellulases . However, most of the oxidants used in the oxidative pretreatment, such as O 3 , H 2 O 2 , and NaClO 2 , are not recyclable or easily regenerated.…”
Section: Figurementioning
confidence: 99%
“…[8] Lignincan be removed by various chemical processes, among them an oxidative process can substantially modifyt he lignin structure and decreases urface hydrophobicity that has been knownasamain factorf or non-productive adsorption of cellulases. [9] However, most of the oxidantsu sedi nt he oxidative pretreatment, such as O 3 ,H 2 O 2 ,a nd NaClO 2 ,a re not recyclable or easily regenerated.Polyoxometalates (POMs) are polyatomic ions consisting of three or more transition metal oxyanions linked together by shared oxygen atoms.T hey have distinct properties such as robust oxidative degradation abilitya nd acidity,w ith great potential as electron reservoirs.POMs have been used as catalysts for selective oxidative delignification of pulps using oxygen [10] (Figure 1A). This is because POMs generally have ah igher redox potential than the lignin structures for oxidizing lignin, but lower potentials than oxygen, thereby allowing their possible re-oxidationbyo xygen.…”
mentioning
confidence: 99%